Correlation between Carotid Intimal-Media Thickness and Coronary Artery Disease Severity in Stable Coronary Artery Disease Patients - Muhammad Haris; Hariadi Hariawan; Muhamad Taufik Ismail; Abdus Samik Wahab (ACI (Acta Cardiologia Indonesiana), 2017)
Background: Atherosclerosis is a fundamental process in the natural course of coronary heart disease (CHD), carotid artery disease and peripheral artery disease. Atherosclerosis is caused by an imbalance of homeostasis in the level of the endothelial layer and the presence of risk factors. The manifestations of coronary atherosclerosis have a wide spectrum of diseases, ranging from subclinical to clinical phases. In patients without CHD symptoms, changes incarotid artery morphology include carotid intimal-media thickness (CIMT) and carotid plaques which correlated with CHD. This study aims to see the relationship between CIMT with the severity of coronary lesions in stable coronary artery disease.Methods: The study was an analytical observational research using cross sectional design. Data was taken by consecutive sampling from outpatient hospital clinic. The CIMT score was obtained from the examination of a communis carotid artery using a B-mode ultrasound device. The value ofCIMT is divided into 2 groups based on the value of the sensitivity curve and the specifcity curve. The value of Syntax was obtained from the catheterization laboratory and the factors that inﬂuenced it were recorded. Pearson correlation test is used to analyze the relationship of CIMT and Syntax value. The logistic regression test used for multivariate test.Results: Of the 58 patients, there were 33 subjects who had a CIMT score of > 0.71 mm and 25 subjects who had a CIMT score of ≤0.71 mm. There is a positive correlation (r = 0.403; p <0.05) between CIMT value and Syntax value. Subjects who have high Syntax value in the group with a CIMT value >0.71 mm compared to CIMT values ≤0.71 mm were 29 versus 4 (RR: 1.831; CI 95%:1.194-2.807; p = 0.01). A multivariate test showed CIMT consistently as a independent risk factor of Syntax value in stable coronary artery disease with RP 5.27 (CI 95%: 1.306-25.047; p = 0.021).Conclusion: The increase in CIMT value has a signifcant positive correlation with the Syntax value. A CIMT > 0.71 mm is a independent risk factor of high Syntax value in stable coronary artery disease with prevalence ratio 5.27